2016
DOI: 10.1039/c6sm01509c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption isotherms of charged nanoparticles

Abstract: We present theory and simulations which allow us to quantitatively calculate the amount of surface adsorption excess of charged nanoparticles to a charged surface. The theory is very accurate for weakly charged nanoparticles and can be used at physiological concentrations of salt. We have also developed an efficient simulation algorithm which can be used for dilute suspensions of nanoparticles of any charge, even at very large salt concentrations. With the help of the new simulation method, we are able to effi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Overcharging of pure proteins is usually explained by the adsorption of ions at proteins. 1,5,33,[50][51][52][53][54][55][56][57][58][59][60][61][62] However, this argumentation falls short, as the pre-and post-incubation pH has rarely been considered for Au@protein systems [63][64][65] or for pure proteins. 9,20 When the post incubation pH was measured, huge pH effects were observed that changed the protein charge drastically.…”
Section: Resultsmentioning
confidence: 99%
“…Overcharging of pure proteins is usually explained by the adsorption of ions at proteins. 1,5,33,[50][51][52][53][54][55][56][57][58][59][60][61][62] However, this argumentation falls short, as the pre-and post-incubation pH has rarely been considered for Au@protein systems [63][64][65] or for pure proteins. 9,20 When the post incubation pH was measured, huge pH effects were observed that changed the protein charge drastically.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic Force Microscopy (AFM 5600LS, Agilent, Santa Clara, California, USA) was used to provide 2-dimensional and 3-dimensional AFM of both AgNPs and either Ag-FNP and Ag-MNP. First, samples were subjected to ultrasound waves for one hour, a condition of 60 kHz, and an amplitude of 85% and 0.6 of a cycle (UP400S manufactured by Hielscher, Teltow, Germany); then, a thin film was created using a spin coating instrument model Laurell-650Sz under the condition of 820 rpm under vacuum [41].…”
Section: Characterization Of Both Agnps and Nanocomposites (Ag-fnp Ag-mnp)mentioning
confidence: 99%
“…Samples were degassed at 50 • C for 3 h. Nitrogen was the adsorbate model, with the following specifications: cross-sectional area (16.2 Å 2 /molec), molecular weight (28.0134 g), bath temperature (77.35 K), magnetic susceptibility (2 (mL/mol) × 10 −29 ), critical pressure (33.5 atm), critical temperature (126.2 K), and supercritical adsorption. In addition, the isotherm curves of AgNPs and Ag-protein nanocomposites were constructed as described by [41].…”
Section: Characterization Of Both Agnps and Nanocomposites (Ag-fnp Ag-mnp)mentioning
confidence: 99%
“…How relevant these correlations will be depends on a fine tuning between ionic charge, size and the dielectric constant of the solvent they are embedded into 29 . The relative strength of electrostatic correlations can be quantified via the so-called coupling parameter [39][40][41][42] , which measures the ratio between the electrostatic energy at ionic contact and the ionic thermal energy. Even if the ions bear relatively large charges (e .g.…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, one such mPB has been designed by dos Santos et al 73 in order to account for finite size effects on the adsorption of charged hard nanoparticles at a charged interface.…”
Section: Introductionmentioning
confidence: 99%